Analysis Evaluation of Intergovernmental Cooperation in Recognition of Prior Learning (RPL) Program in Bojonegoro Regency, Indonesia - Ma'ruf, Muhammad Farid; Said, Abdullah; Mindarti, Lely Indah; Putra, Fadillah; Esmael, Salma Tarek Eid (JPSI (Journal of Public Sector Innovations), 2024)
This study evaluates the implementation of the Recognition of Prior Learning (RPL) Program in Bojonegoro Regency, Indonesia, using the Context, Input, Process, Product (CIPP) evaluation model for village apparatus. This program is a collaboration between the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration Indonesia (Kemendesa PDTT) with Surabaya State University (Unesa) and Yogyakarta State University (UNY). The RPL program aims to improve the competence of village apparatus and recognize their work experience by converting into academic credit. Using a qualitative research approach and using the CIPP evaluation model. An evaluation analysis was carried out on the collaboration between the regional government of Bojonegoro district and the university (Unesa) and the Ministry of Villages-PDTT on implementing the Village RPL program. The source of data comes from informants extracted from the Ministry of Villages-PDTT, Bojonegoro Regency Government, and Surabaya State University (Unisa) using interviews, observation, and distributing several questionnaires to RPL program participants. The findings show, iIn terms of “Context,” this study identifies the importance of the RPL program as a solution to the education and competency gaps of village aparatus. Strengthening village government authority requires village officials to have administrative and managerial skills to manage village development. In the “Input” aspect, the program is designed with a collaborative strategy between educational institutions and local governments through the implementation of higher education by providing scholarships for village aparatus. The implementation of this RPL also follows guidelines that set out the requirements and assessment process for participants. In term of “Process”. this program includes the assessment of participants' portfolio documents by universities to determine the equivalence of learning outcomes with related study programs. Participants then attended online lectures held in accordance with the academic schedule, although there were obstacles, such as digital literacy and limited internet networks. In terms of “Product” analysis showed that this program had a positive impact on improving the competence of village officials. Participants acknowledged new knowledge and skills relevant to their duties, although there was a need for improvement in the provision of information regarding the study programs to be taken by participants. The study recoend to encourage strengthening inter-agency cooperation to overcome technical obstacles and improve the effectiveness of RPL implementation